Prospek Cyber Notary Sebagai Media Penyimpanan Pendukung Menuju Profesionalisme Notaris - Syamsir Syamsir; elita rahmi; Yetniwati Yetniwati (Magister Kenotariatan, Universitas Jambi, 2019)
Legal Procedure in the Implementation of Cyber ​​Notary in the future is closely related to legal development, community development and the development of science and technology. The development of technology and information is a phenomenon that continues to grow, can hardly be balanced with the development of law. Notary is a certain position that runs the profession in legal services to the community, needs to get protection and guarantees in order to achieve legal certainty. The development of technology and information is characterized by the era of informatics technology that introduces cyberspace, namely with the presence of Interconnected networks (Internet), this communication does not use media such as paper and the actual pens in Law are a tool for legal actions. In the Notary Protocol, there are minuta deeds in the form of a collection of documents which are State Archives that must be stored and maintained by a Notary and can be used as evidence in the event of legal actions in civil law. Digitally documenting (storage media) and CCTV as supporting documents for legal actions in signatories Contract agreements and as a Notary Protocol can be done using a computer / device and / or a computerized system or using the Internet. Computers are human tools in completing daily work, both personal work, in government and private offices. Storage media tools / equipment for decoding archives that are currently and are still being used in the form of diisket, laser disk, CD, DVD, HD-DVD and Blu-Ray, Memory Card, Memory Card, Flashdisk. USB Flash Drive, Hard Disk, External Hard Disk, and storage of data / documents Archives online, known as Cloud Storage. CCTV can be used as a supporting document for legal actions in signatories to contract agreements and as a notary protocol, because CCTV can record activities that are being carried out in the form of a video record, can store documents electronically and can connect objects to one another.